Monitoring of social clauses in the Democratic Republic of Congo 2011-2020 - Tsanga, R.; Cerutti, P.O.; Njumboket, I.; Tibaldeschi, P. (Center for International Forestry Research, 2021)
The bulk of financial resources devoted to social clause infrastructure projects is allocated to those in the education sector, accounting for about USD 4 million (74%); this is followed by 20% allocated for healthcare infrastructure, 4% for road infrastructure and 1% for water supply infrastructure. Cumulatively across the whole monitoring period (2011-2020), an estimated 36,466 students were direct beneficiaries of the education sector. A total of 127 schools, 85 health centres, 27 administrative buildings, 11 water points and 436 kilometres of road were built within the framework of social clauses.